Education and Social Mobility For Orang Asli Papua - Alfath Bagus Panuntun El Nur Indonesia (PCD Journal, 2021)
Papuan human resources are complicated due to educational barriers that make it difficult for indigenous Papuans (OAP) to achieve upward social mobility. Many factors have contributed to these educational barriers, including poverty, conflict and war, a lack of teachers, and poor infrastructure. These obstacles should be solved through the main feature of the Special Autonomy Law (SAL), namely the "special autonomy fund". Although these funds have been rolled out in Papua since 2001 to address inequality and improve OAP's human resources, their conditions have not improved significantly. This qualitative study explored the experiences of Mappi and Puncak OAPs involved in education financed by the special autonomy fund through cooperation between the government and the university. The findings revealed the positive effect of SAL on reducing educational barriers and increasing social mobility for OAPs, but there are still some areas that needed to be improved. OAPs’ experience showed that formal education was the main determining factor to upward social mobility. This article also highlighted several areas for change, such as informal education support that needed to be improved; promoting equal development in both the coast and the highlands; increased community participation; and strengthening the political will. Recommendations are also offered.